Community Perceptions of the Ruwatan Rambut Gimbal Tradition in the Dieng Highlands, Wonosobo Regency - Adyesta Nareswari; Puji Laksono (Universitas Pakuan, 2026)
The tradition of ruwatan for children with naturally curly hair is a cultural heritage of the Dieng community that is still preserved as part of their belief system and local cultural identity. This tradition is associated with children who have naturally curly hair and are believed to be connected to the ancestors of Dieng. This study aims to analyze the community’s interpretation of the “ruwatan rambut gimbal” tradition, their views on children with curly hair, the values embedded in the tradition, and the urgency of its preservation. The study employs a qualitative approach using descriptive methods. Data were collected through interviews, observations, and literature review, and were analyzed using qualitative data analysis techniques, including data reduction, data presentation, and drawing conclusions. The results indicate that the community interprets the “ruwatan rambut gimbal” as a cultural heritage passed down through generations and as a symbol of respect for their ancestors. This tradition embodies cultural, spiritual, and social values, as well as a sense of community and mutual cooperation, which strengthen social cohesion within the Dieng community. Furthermore, preserving this tradition is considered important not only for maintaining local cultural identity but also as a cultural asset that contributes to the development of tourism based on local wisdom. These findings confirm that the “ruwatan rambut gimbal” tradition serves cultural, social, and symbolic functions that remain relevant in the lives of the Dieng community amid the dynamics of social change. Keywords: cultural identity, cultural preservation, local wisdom, the Dieng community, the “ruwatan rambut gimbal” ritual.